2021
DOI: 10.1002/tpg2.20102
|View full text |Cite
|
Sign up to set email alerts
|

Unoccupied aerial systems discovered overlooked loci capturing the variation of entire growing period in maize

Abstract: Traditional phenotyping methods, coupled with genetic mapping in segregating populations, have identified loci governing complex traits in many crops. Unoccupied aerial systems (UAS)-based phenotyping has helped to reveal a more novel and dynamic relationship between time-specific associated loci with complex traits previously unable to be evaluated. Over 1,500 maize (Zea mays L.) hybrid row plots containing 280 different replicated maize hybrids from the Genomes to Fields (G2F) project were evaluated agronomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Plant selection at an early stage is challenging due to the impact of weather variability and the time needed for the plant to show discernible traits; however, studies in maize and soybean crops have shown that early phenotypic traits, collected with HTP platforms, can be used as an indicator of yield under optimal conditions [47,48]. In maize, a previous study using the 2017 G2F dataset identified loci associated with controlling plant height at early development, which showed a significant impact on yield prediction [48]. In our study, the use of early phenotypic data and genotype showed varied results, depending on the machine learning model employed, with the multimodal model presenting a higher prediction accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant selection at an early stage is challenging due to the impact of weather variability and the time needed for the plant to show discernible traits; however, studies in maize and soybean crops have shown that early phenotypic traits, collected with HTP platforms, can be used as an indicator of yield under optimal conditions [47,48]. In maize, a previous study using the 2017 G2F dataset identified loci associated with controlling plant height at early development, which showed a significant impact on yield prediction [48]. In our study, the use of early phenotypic data and genotype showed varied results, depending on the machine learning model employed, with the multimodal model presenting a higher prediction accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In P2F1, the yield was consistently lower than other treatments because the hybrids were sown later in the season and experienced heat stress. A study using the same dataset hypothesized that delayed planting in that region of Texas, US, may increase photosynthetic activity, leading to increased plant height and lower yield [48].…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that higher temporal and image resolution were provided in this study by lower flight altitude (25 m) and higher number of flights (13 and 17 time points) to generate the high throughput phenomic data that have been disregarded so far by most of the current literatures. Higher temporal and image resolutions were proposed to be important in predicting complex traits with higher accuracies, followed by the number of wavelengths and sensors 57 , 58 . Moreover, temporal resolution in high throughput phenomic data is required to dissect the growth stages in greater detail, particularly when the determination of critical time points as selection criteria are a goal in plant breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous GWAS have been performed after the sequencing data and the associated rice seed materials became available (for example, [ 37 , 38 ]). Additionally, with the ease of high throughput phenotyping, GWAS has become a more attractive tool to dissect the molecular genetic control of breeding-relevant traits, for example, in rice [ 39 ], sorghum [ 40 ], and corn [ 41 ].…”
Section: Integrating Genetic Mapping and Genomics For Candidate Gene ...mentioning
confidence: 99%